2021
DOI: 10.1007/s12015-021-10159-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Homing of Human Dental Pulp Stromal Cells in Head and Neck Cancer

Abstract: Background: Head and neck cancer (HNC) is one of the most common cancers, associated with a huge mortality and morbidity. In order to improve patient outcomes, more e cient and targeted therapies are essential. Bone marrow-derived mesenchymal stromal cells (BM-MSCs) express tumour homing capacity, which could be exploited to target anti-cancer drug delivery to the tumour region and reduce adverse sideeffects. Nevertheless, dental pulp stromal cells (DPSCs), an MSC-like population present in teeth, could offer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 109 publications
(122 reference statements)
0
4
0
1
Order By: Relevance
“…It has been previously reported that hDPSCs exhibit significant migration towards tumor cells in in vitro assays. However, the tumor tropism of hDPSCs could not be confirmed in vivo following intravenous, intraperitoneal, or peritumoral injection under the tested experimental conditions [ 16 ]. In contrast, our results confirmed the tumor tropism of hDPSCs and demonstrated the anti-cancer efficacy of YSCH-01/hDPSC in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that hDPSCs exhibit significant migration towards tumor cells in in vitro assays. However, the tumor tropism of hDPSCs could not be confirmed in vivo following intravenous, intraperitoneal, or peritumoral injection under the tested experimental conditions [ 16 ]. In contrast, our results confirmed the tumor tropism of hDPSCs and demonstrated the anti-cancer efficacy of YSCH-01/hDPSC in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most well-known signaling pathway is the CXCR4/SDF-1α axis [ 15 ]. However, a study investigating subcutaneous, intravenous, and peritumoral injection of hDPSCs into subcutaneous tongue cancer models revealed no evidence of stem cell presence in the tumor tissue [ 16 ]. This observation suggests that hDPSCs may not effectively migrate into tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the regeneration of damaged tissue, tumors exert chemotactic effects on MSCs, affecting their recruitment to tumor sites[ 75 - 77 ]. Current studies have shown that MSCs have bidirectional, anti-cancer and pro-cancer, regulatory effects, which raises safety concerns for clinical application.…”
Section: Safety Issues Regarding Dsc-based Therapymentioning
confidence: 99%
“…In the treatment of these diseases using DPSCs, injection is one of the more commonly used forms. Stem cell injections are the easiest cell therapy products to prepare, and the commonly used vehicles at present for resuspension of stem cells is phosphate-buffered saline[ 69 - 73 ], Hank's Balanced Salt Solution[ 15 ], normal saline[ 14 , 67 , 74 - 76 ], and modified medium[ 66 , 68 , 77 - 79 ]. These mediators have no therapeutic effect and only serve as transport vectors for stem cells, so it is possible to observe the monotherapy effect of transplanted stem cells and rule out the influence of carriers.…”
Section: Derivatives Of Dpscsmentioning
confidence: 99%